In vitro evaluation of the anticancer effects of green gold nanoparticles in breast cancer cell lines - Osman, Ridwaan (Stellenbosch : Stellenbosch University, 2025)

(untitled)
Thesis (MEngSc)--Stellenbosch University, 2025.